The Evolution of Proteomics from 2010 to 2020 - Kamal, Razan (International Journal of Innovative Research in Medical Science, 2022)
This paper presents a brief introduction to proteomics and defining the concept of proteomics. After that, listing some important techniques that used in proteomics from 2010 to 2020. It explores proteomics’ techniques advantages and limitations, and how it has advanced in this past decade. Finally, this paper outlines the proteomics’ evolution and its methods, techniques and modifications made in that period. This paper aim is to analyse and identify the changes and transitions that proteomics has experienced from 2010 to 2020.